Living Our Research Through Indigenous Scholar Sisterhood Practices. (November 2018) - Shotton, Heather J.; Tachine, Amanda R.; Nelson, Christine A.; Minthorn, Robin Zape-tah-hol-ah; Waterman, Stephanie J.
In this article, we explore the concept of Indigenous scholar sisterhood practices and its powerful role in affirming Indigenous women to survive and thrive in the act of research and the larger academic landscape. We address how we, as Indigenous women scholars, extend beyond transactional validity practices in qualitative research and engage in a collective form of validity that is holistic and grounded in Indigenous ways of knowing. We explore what it means to live our research and reclaim academic spaces among a collective sisterhood, as we grapple with questions of what valid and rigorous research looks like from an Indigenous perspective. Recognizing that attempts to decolonize methodological spaces can be complex and tempered with struggles, we provide personal accounts of Indigenous scholar sisterhood practices of love, prayer, vulnerability, and resistance and protection used to maneuver through this space together. As Indigenous women scholars, we conclude by reimagining the value of collective work as a means to not only survive academia but lift up our communities.